Haemodialysed patient with lung cancer in the COVID-19 era: a clinical challenge. Issue 7 (29th July 2021) - Carvalho, Tomás de Paiva; Trinca, Francisco; Cardoso, Teresa; Dinis, Rui
Abstract : A 66-year-old man was referred to the oncological pneumology consultation due to a mass in the right upper lobe observed in a routine X-ray of the chest. The CT scan confirmed a mass in the same location. The biopsy revealed a lung adenocarcinoma. It was decided to start chemotherapy adapted to kidney function. In April 2020, the patient contracted SARS-CoV-2 infection and developed bilateral pneumonia with partial respiratory failure. He was transferred to the intensive care unit, where he had a positive evolution. In the next 5 months, there was a clinical improvement; however, the CT scan of the chest showed disease progression. After a new multidisciplinary approach, it was decided to start a second line with atezolizumab. After four cycles of atezolizumab, there was a clear clinical improvement, and a reduction by more than 50% in the tumour size, without significant adverse effects.